Acceptance and affordability of malaria vaccines: issues relating to hesitancy and willingness to pay amongst Nigerian parents of under-five children - Obi Peter Adigwe; Godspower Onavbavba (Malaria Journal)
Abstract Background With the recent approval of the malaria vaccine by the World Health Organization, it is expected that global acceptance and subsequent uptake of the intervention can help to reduce the burden of the disease in Africa. This study adopted a proactive approach in assessing parents' acceptance of the malaria vaccine, alongside their willingness to pay for the novel public health intervention. Methods A national cross-sectional survey was undertaken in Nigeria using a questionnaire as the data collection instrument. The study tool was administered to parents of child-bearing age. Descriptive and inferential statistical analyses were performed using the Statistical Package for Social Sciences (SPSS) software version 25. Results A total of 1413 valid responses were received with male (49.5%) and female (50.5%) participants represented by similar proportions. Close to two-thirds (62.5%) of the participants were between the ages of 31 and 40 years, and 47.4% of the participants were educated up to national diploma level. More than two-thirds (69.6%) of the participants indicated that they were worried about side effects that may be associated with the malaria vaccine. A strong majority (90%) of the participants indicated that the vaccine should be administered at no cost to citizens, while 46.7% of the respondents were willing to pay for the malaria vaccination. Levels of education attained by the respondents influenced their willingness to pay for malaria vaccination. This variable also underpinned participants'  reasons for non-acceptance of the vaccine. Those who attained only primary and secondary levels of education were significantly more likely to reject the malaria vaccine because they were against vaccines in general (AOR = 6.63; 95% CI = 1.33 – 39.25; p = 0.021). Conclusion This study provides critical novel insights which could influence vaccination efforts aimed at reducing the burden of malaria in Nigeria, as well as similar settings.